2015
DOI: 10.1080/10643389.2015.1061881
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of endocrine disrupting compounds in aqueous environment and their bacterial degradation: A review

Abstract: Endocrine-disrupting compounds (EDCs), represented by steroidal estrogens (estrone (E1), 17β-estradiol (E2), estradiol (E3) and 17α-ethinylestradiol (EE2) and xenoestrogens (bisphenol A (BPA) and nonylphenol (NP)), are pollutants with estrogenic activity at very low Downloaded by [University of Sussex Library] at 01:37 14 August 2015 ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 2concentrations and are emerging as a major concern for water quality. They enter into aqueous environment mainly through discharge of wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(61 citation statements)
references
References 225 publications
2
59
0
Order By: Relevance
“…This study resulted in the characterization of estrogen transformation by environmental isolates of two genera not previously known to transform estrogens, Rhizobium and Sphingopyxis , both belonging to the class Alphaproteobacteria in the phylum Proteobacteria. Various members of the class Alphaproteobacteria are well known for their abilities to degrade estrogens (reviewed in Yu et al [2013] and Zhang et al [2016]); however, these two genera have never previously been implicated in estrogen transformations. Rhizobium is a member of the family Rhizobiaceae, which includes known estrogen‐transforming bacteria in the genera Aminobacter (Yu et al, 2007) and Phyllobacterium (Pauwels et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study resulted in the characterization of estrogen transformation by environmental isolates of two genera not previously known to transform estrogens, Rhizobium and Sphingopyxis , both belonging to the class Alphaproteobacteria in the phylum Proteobacteria. Various members of the class Alphaproteobacteria are well known for their abilities to degrade estrogens (reviewed in Yu et al [2013] and Zhang et al [2016]); however, these two genera have never previously been implicated in estrogen transformations. Rhizobium is a member of the family Rhizobiaceae, which includes known estrogen‐transforming bacteria in the genera Aminobacter (Yu et al, 2007) and Phyllobacterium (Pauwels et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A diversity of bacteria is known to transform estrogens, including members of the phyla Proteobacteria, Bacteroidetes, Firmicutes, and Actinobacteria (reviewed in Yu et al [2013] and Zhang et al [2016]). Many of these microorganisms can co‐metabolically oxidize E2 to E1, and some can degrade estrogens to small, nontoxic products, by using estrogens as sole carbon sources and electron donors for heterotrophic growth, with examples including Novosphingobium strain ARI‐1 (Fujii et al, 2002), Sphingomonas sp.…”
mentioning
confidence: 99%
“…It has been shown that their detection in wastewater adds to the increased antimicrobial resistance, as well as toxicity due to Clarithromycin and Erythromycin. Estradiol is also not fully degraded, and its presence in surface waters [39] affects sea life [41]. As wastewater treatment is suggested to not completely remove the concentrations of these substances in the aquatic environment [14,[16][17][18]39], the solution could be to manage the pollution at the source, which is the human, veterinarian, and agricultural intake and use.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of 2000s, physical and chemical processes were used to remove such contaminants from wastewater, but they are commonly expensive and may generate a large volume of sludge [4]. On the other hand, biological wastewater treatments exploiting bacteria or fungi are attractive options as they could be cost-effective and environmentally friendly [5,6]. However, most of EDCs are present in the environment at a concentration level under the biodegradation threshold of bacteria [7] and /or are recalcitrant to their treatment [8].…”
Section: Introductionmentioning
confidence: 99%